Long-term treatment with subcutaneous immunoglobulin in multifocal motor neuropathy - Gentile, Luca (Sci Rep, 2021)
Multifocal motor neuropathy (MMN) is a rare disease with a prevalence of less than 1 per 100,000 people. Intravenous immunoglobulin (IVIG) therapy, performed for a long-term period, has been demonstrated able to improve the clinical picture of MMN patients, ameliorating motor symptoms and/or preventing disease progression. Treatment with subcutaneous immunoglobulin (SCIg) has been shown to be as effective as IVIG. However, previously published data showed that follow-up of MMN patients in treatment with SCIg lasted no more than 56 months. We report herein the results of a long-term SCIg treatment follow up (up to 96 months) in a group of 8 MMN patients (6 M; 2F), previously stabilized with IVIG therapy. Clinical follow-up included the administration of Medical Research Council (MRC) sum-score, the Overall Neuropathy Limitation Scale (ONLS) and the Life Quality Index questionnaire (LQI) at baseline and then every 6 months. Once converted to SCIg, patients’ responsiveness was quite good. Strength and motor functions remained stable or even improved during this long-term follow-up with benefits on walking capability, resistance to physical efforts and ability in hand fine movements.